PERKEMBANGAN KINERJA KEUANGAN PT PERTAMINA (Persero) - Wiryanti, Tutik; B. Sulistiyono, Bambang (Feb Universitas Dirgantara Marsekal Suryadarma, 2016)
PT Pertamina (Persero) is a State-owned Enterprise (SOE) whose shares are not listed on the stock exchange, so the Company does not present information about the stock price,number of outstanding shares, market capitalization, highest and lowest price, closing price, and trading volume.The share holder owned 100% by Government of the Republic of Indonesia, the companyâ€™s shares are not to be traded. Pertamina improved its performance based on the strategy of â€œaggressive upstream, profitable downstream.â€ As a world-class company, Pertamina transformed challenges into opportunities. Pertamina maximized efficiency and optimized production. On the other hand, the optimized performance was enhanced in line with strengthening the performance of good corporate governance (GCG).The rise in crude oil production and the acquisition of Murphy Oil Corp.assets in Malaysia was one of the good achievements in 2014. In general, Pertaminaâ€™s financial performance, financial ratios and operational performance were quite satisfactory, although some achievements did not meet expectations. Its performance and achievements, Pertamina will move faster. The theme of â€œInspiring Indonesia to the Worldâ€ in Annual Report 2014 was chosen to convey the moving-forward of global energy issues and to inspire others as an energy provider. Keywords : Financial Performance, Development